Physical and Organoleptic Properties of Freeze-dried Local Beans and Salak Yogurt Powder: Physical and Organoleptic Properties of Freeze-dried Local Beans and Salak Yogurt Powder - Sumarto; Ani Radiati; Irma Nuraeni (Journal of Tropical Life Science, 2023)
Yogurt is one of the most popular fermented dairy products worldwide, with huge consumer acceptance due to its health benefits. While its shelf life is still relatively low, freeze-drying could extend the shelf life of yogurt. Other non-milk raw materials that can be an alternative substrate in yogurt are local Indonesian beans, namely Mung bean and Garut red bean. Additionally, yogurt can be added to the fiber- and carbohydrate-rich Manonjaya salak flour to produce a synbiotic product. Hence, this study aimed to produce yogurt powder comprising local nuts and Manonjaya salak through a freeze-drying process, which physical properties are organoleptically acceptable and meet Indonesian standards. In this study, the yogurt powder comprising the local Garut red- and Mung beans mixed with Manonjaya salak flour was compared to fresh yogurt as the control, plus yogurt powders from milk and nuts, as well as synbiotic yogurt powder from nuts, and Manonjaya salak flour. The physical properties of the resultant yogurt were tested for pH, %brix, moisture content, and organoleptic properties with hedonic testing. The findings revealed that the freeze-dried yogurt powder comprising Garut red- and Mung beans mixed with Manonjaya salak flour exhibited acceptable water content (10.39) with a 5.57 %brix and a final pH of 5.0, and was organoleptically acceptable by panelists. The physical and organoleptic properties of the Garut red-, mung beans, and Manonjaya salak flour yogurt power met the Indonesian national standards.